The population genetics of sporophytic self-incompatibility in Senecio squalidus L. (Asteraceae): the number, frequency, and dominance interactions of S alleles across its British range. - Brennan, A; Harris, S; Hiscock, S (2006)
Sporophytic self-incompatibility (SSI) was studied in 11 British Senecio squalidus populations to quantify mating system variation and determine how its recent colonization of the United Kingdom has influenced its mating behavior. S allele number, frequency, and dominance interactions in populations were assessed using full diallels of controlled pollinations. A mean of 5.1 S alleles per population was observed, and no population contained more than six S alleles. Numbers of S alleles within populations of S. squalidus declined with increasing distance from the center of its introduction (Oxford). Cross-classification of S alleles allowed an estimate of approximately seven and no more than 11 S alleles for the entire British S. squalidus population. The low number of S alleles observed in British S. squalidus compared to other SI species is consistent with the population bottleneck associated with S. squalidus' introduction to the Oxford Botanic Garden and subsequent colonization of Britain. Extensive S allele dominance interactions were observed to be a feature of the S. squalidus SSI system and may represent an adaptive response to improve limited mate availability imposed by the presence of so few S alleles. Multilocus allozyme genotypes were also identified for individuals in all populations and geographic patterns of S locus and allozyme loci variation investigated. Less interpopulation structure was observed for the S locus than for allozyme diversity--a finding indicative of the effects of negative frequency-dependent selection at the S locus maintaining equal S phenotypes within populations and enhancing effective migration between populations.